Rehabilitation of cognition and psychosocial well-being – a better life with epilepsy (ReCaP-ABLE): a protocol for a randomized waitlist-controlled trial - Puteikis, Kristijonas; Jakonienė, Asta; Jasionis, Arminas; Wolf, Peter; Mameniškienė, Rūta (Frontiers in Neurology, 2023)
Despite advances in the understanding of cognitive dysfunction among people with epilepsy (PWE), evidence for cognitive rehabilitation in epilepsy (CoRE) remains scarce. We present the protocol of a randomized waitlist-controlled trial (ClinicalTrials.gov ID NCT05934786) of a psychological-behavioral intervention aiming to ameliorate quality of life as well as cognitive functioning in a mixed PWE sample. The study is set at Vilnius University Hospital Santaros Klinikos and will offer adult PWE six individual and two group sessions led by a certified psychologist and directed toward improving memory, attention, self-regulation, mood and quality of life. The trial is expected to address major gaps in the literature by providing novel evidence on the effectiveness of CoRE in patients with genetic generalized epilepsies, the importance of epilepsy-specific factors for the response to CoRE, the impact of CoRE on long-term memory as well as its maintenance effects.